(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Chronic septic arthritis of the hip in children is an uncommon but serious condition, often resulting from delayed diagnosis or inadequate initial treatment. Unlike acute presentations, chronic disease may present with subtle clinical features, leading to progressive joint destruction, deformity, and long-term functional impairment. Early recognition and appropriate management are essential to minimize morbidity. Objectives: To evaluate the clinical presentation, radiological features, histopathological findings, and short-term functional outcomes of paediatric patients diagnosed with chronic septic arthritis of the hip. Materials and Methods: This observational clinicoradiological and histopathological study was conducted at a tertiary care teaching hospital over a ten-month period from February 2025 to November 2025. A total of 32 paediatric patients aged 2–14 years with symptoms persisting for more than four weeks were included. All patients underwent detailed clinical evaluation, laboratory investigations, radiological assessment including plain radiography and selective magnetic resonance imaging, surgical arthrotomy and debridement, and histopathological examination of synovial tissue. Functional outcomes were assessed at 2-month follow-up using modified Moon’s criteria. Results: The mean age of patients was 6.8 years, with a male predominance. Limp and restricted hip movements were the most common presenting features. Radiological evaluation revealed joint space narrowing and femoral head changes in most patients, while MRI identified associated osteomyelitis and soft tissue involvement in selected cases. Histopathological examination confirmed chronic inflammatory changes in all patients, with no evidence of tuberculosis. At short-term follow-up, 68.7% of patients achieved good to excellent functional outcomes, while poorer outcomes were associated with advanced disease at presentation. Conclusion: Chronic septic arthritis of the hip in children remains a diagnostic and therapeutic challenge due to delayed presentation and subtle clinical features. A combined clinicoradiological and histopathological approach, along with timely surgical intervention, results in satisfactory short-term functional outcomes. Early diagnosis and prompt management are crucial to reduce joint damage and improve outcomes in affected children.